2017
DOI: 10.5423/ppj.oa.04.2017.0073
|View full text |Cite
|
Sign up to set email alerts
|

Diffusible and Volatile Antifungal Compounds Produced by an Antagonistic Bacillus velezensis G341 against Various Phytopathogenic Fungi

Abstract: The aim of this study was to identify volatile and agar-diffusible antifungal metabolites produced by Bacillus sp. G341 with strong antifungal activity against various phytopathogenic fungi. Strain G341 isolated from four-year-old roots of Korean ginseng with rot symptoms was identified as Bacillus velezensis based on 16S rDNA and gyrA sequences. Strain G341 inhibited mycelial growth of all phytopathogenic fungi tested. In vivo experiment results revealed that n-butanol extract of fermentation broth effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(76 citation statements)
references
References 52 publications
4
66
0
Order By: Relevance
“…Previous research has shown that the B . velezensis strain can be used as a biocontrol agent for various plant diseases caused by phytopathogenic fungi, and it can effectively inhibit the growth of Fusarium by producing a variety of antimicrobial peptides 40 42 . However, a study on the application of B .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the B . velezensis strain can be used as a biocontrol agent for various plant diseases caused by phytopathogenic fungi, and it can effectively inhibit the growth of Fusarium by producing a variety of antimicrobial peptides 40 42 . However, a study on the application of B .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, an antagonistic interaction between bacteria and fungi would be beneficial to protect plants of agronomical importance against phytopathogenic fungi that reduces the yield and quality of crops (5)(6)(7). One strategy to achieve this goal is to control soilborne plant diseases via the utilization of plant growth-promoting rhizobacteria (PGPRs), which have the ability to maintain the population of plant-pathogenic microbes below the disease threshold level in soil and plant tissues (8)(9)(10)(11)(12). A large number of biocontrol agents have been identified, but to date, Bacillus species, in particular those that belong to the B. amyloliquefaciens/B.…”
mentioning
confidence: 99%
“…These characteristics endow acetoin with a possibility to be large-scale applied to crops in the field. B. velezensis has potential as a good agent for biocontrol of plant diseases by producing VOCs such as acetoin and 2,3-BD (Lim et al 2017). Here, we report that B. velezensis can produce acetoin to trigger IST against O 3 injury in plants.…”
Section: Discussionmentioning
confidence: 73%